2010
DOI: 10.1677/joe-10-0265
|View full text |Cite
|
Sign up to set email alerts
|

Kisspeptin and fertility

Abstract: The kisspeptins are a familyof peptide hormones, which in recent years have been shown to play a critical role in the regulation of the hypothalamic-pituitary-gonadal axis, thus in turn influencing fertility and reproduction. This review examines the physiological role of kisspeptin and the kisspeptin receptor in the control of gonadotrophin and gonadal steroid hormone secretion and the implications of these findings with respect to fertility. In addition, the potential therapeutic use of kisspeptin in the tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(39 citation statements)
references
References 90 publications
0
39
0
Order By: Relevance
“…This possibility was indeed supported by a subsequent study in which P450arom-null mice fed on a soy-free diet indeed became infertile after 1 year with postmeiotic defects, incapable of completing spermiogenesis . In addition, mice with mutations in the kisspeptin signaling pathway [e.g., Kiss1(Ϫ/Ϫ) or Gpr54(Ϫ/Ϫ) mice; kisspeptins are a family of peptide hormones that, together with the kisspeptin receptor (previously known as G-protein-coupled receptor 54), play a critical role in the regulation of the hypothalamic-pituitary-testicular axis, such as in the release of 1) gonadotropin-releasing hormone from the hypothalamus and 2) LH and FSH from the pituitary gland (d'Anglemont de Tassigny and Colledge, 2010;Hameed et al, 2011)] were found to have smaller testes and impaired spermatogenesis versus wild-type animals, lacking spermatids in the epithelium as the result of postmeiotic defects. On the other hand, diets supplemented with phytoestrogens (e.g., genistein and daidzein from soy/soybeans) were shown to have a significant improvement in spermatogenesis over a 7-month period with regard to testis weight and the number of elongated spermatids and spermatozoa (Mei et al, 2011).…”
Section: Tight Junction (Zonula Occludens) and Basal Ectoplasmic Specmentioning
confidence: 99%
“…This possibility was indeed supported by a subsequent study in which P450arom-null mice fed on a soy-free diet indeed became infertile after 1 year with postmeiotic defects, incapable of completing spermiogenesis . In addition, mice with mutations in the kisspeptin signaling pathway [e.g., Kiss1(Ϫ/Ϫ) or Gpr54(Ϫ/Ϫ) mice; kisspeptins are a family of peptide hormones that, together with the kisspeptin receptor (previously known as G-protein-coupled receptor 54), play a critical role in the regulation of the hypothalamic-pituitary-testicular axis, such as in the release of 1) gonadotropin-releasing hormone from the hypothalamus and 2) LH and FSH from the pituitary gland (d'Anglemont de Tassigny and Colledge, 2010;Hameed et al, 2011)] were found to have smaller testes and impaired spermatogenesis versus wild-type animals, lacking spermatids in the epithelium as the result of postmeiotic defects. On the other hand, diets supplemented with phytoestrogens (e.g., genistein and daidzein from soy/soybeans) were shown to have a significant improvement in spermatogenesis over a 7-month period with regard to testis weight and the number of elongated spermatids and spermatozoa (Mei et al, 2011).…”
Section: Tight Junction (Zonula Occludens) and Basal Ectoplasmic Specmentioning
confidence: 99%
“…1; reviewed in Clarke (2011), Hameed et al (2011), Wahab et al (2011b, George & Seminara (2012), Pinilla et al (2012) and Terasawa et al (2013)). The finding of the involvement of KP and its receptor Kiss1r in the initiation and maintenance of reproduction is considered as one of the most important discoveries made in the field of reproductive neuroendocrinology (Seminara & Kaiser 2005).…”
Section: Role Of Kp In Regulation Of Reproductionmentioning
confidence: 99%
“…Studies on functional analysis have demonstrated the fundamental role of KiSS-1 in multiple process include i.e. sexual differentiation of brain, regulation of gonadotropin secretion via gonadotropinreleasing hormone (GnRH) neurons, action on sex steroids, metabolic regulation of fertility, essential for initiation of human puberty and also maintenance of adult reproduction (Roa and Tena, 2007;Oakley et al, 2009;Pineda et al, 2010;Hameed et al, 2011;TenaSempere et al, 2012). These divulge of KiSS-1 gene and KPs regulate a wider range of effects in the body and interestingly its role in the suppression of metastasis in a variety of cancers appears to be the most important site of action (Makri et al, 2008;Li et al, 2012).…”
Section: Discovery Of Kisspeptins and Kiss-1mentioning
confidence: 99%